Stock market volatility during dividend announcement a case of selected scripts - S, POORNIMA; V, CHITRA (Journal of Management and Science, 2012)
An attempt has been made in this paper to explain the stock market volatility at the individual script level and at the aggregate indices level. The empirical analysis has been done by using Generalised Autoregressive Conditional Heteroscedasticity (GARCH) model. It is based on daily data for the time period from January 2007 to December 2009. The analysis reveals the same trend of volatility in the case of aggregate indices and three different sectors such as Banking,Information Technology and Cement. The GARCH (1,1) model is persistent for all the five aggregate indices and individual company.